Criminal Law Enforcement of Phising Attacks on Online Banking Services - Aryono; Jaco Barkhuizen (LPPM Universitas Duta Bangsa Surakarta, 2021)
The high rate of fraud crimes has a negative impact on bank customers. Where the higher the crime rate, the customers need a high level of system security, because many attackers or phisers are interested in exploiting customer data if the security level is low. In addition, legal or statutory powers are also needed in dealing with these crimes. In this study, the research method used is juridical or normative research methods. This research method uses research on existing library materials to solve problems. The approach method used in this research is to use the statutory regulatory approach. In this study using primary legal materials and secondary legal materials: 1. Primary legal materials are materials that have juridical binding power, such as statutory regulations, court decisions, and agreements. The legal materials used include the Criminal Code. 2. Secondary legal materials are materials that do not have juridical binding power, namely draft laws and regulations, literature, and journals related to the focus of research. E. Legal Material Analysis Techniques Analysis of the legal materials used in this research is qualitative data analysis including data classification activities in accordance with legal issues and provisions, then editing, presenting the results of the analysis in narrative form, and drawing conclusions. Law enforcement of phishing attacks on this online banking service is in the form of: Criminal threats for the perpetrator (phishers) are regulated in accordance with the following provisions: 1) According to Article 378 of the Criminal Code, it explains that